Efficacy of Oral Sulfate Tablet and 2 L-Polyethylene Glycol With Ascorbic Acid for Bowel Preparation: A Prospective Randomized KASID Multicenter Trial - Jung, Yunho; Kim, Hyun Gun; Yang, Dong-Hoon; Kang, Hyoun Woo; Park, Jae Jun; Baek, Dong Hoon; Chun, Jaeyoung; Gweon, Tae-Geun; Goong, Hyeon Jeong; Kwak, Min Seob; Lee, Hyun Jung; Park, Soo-Kyung; et al. (Journal of Korean medical science, 2024)
Oral sulfate tablets (OSTs) are bowel preparation agents that combine oral sulfate solution and simethicone. This study compared the efficacy, tolerability, and safety of OST compared to 2 L-polyethylene glycol plus ascorbic acid (2 L-PEG/ASC). This prospective, randomized, controlled, single-blinded, multicenter, noninferiority trial enrolled 211 healthy adults who underwent colonoscopy between May 2020 and September 2022 at 13 university hospitals. The bowel cleansing rate was assessed using the Boston Bowel Preparation Scale (BBPS) and Harefield Cleansing Scale (HCS), and the preparation agents were administered in split regimens. The total BBPS score (8.2 ± 1.5 vs. 7.8 ± 1.4, = 0.040) and the high-quality bowel cleansing rates in the right colon (73.2% vs. 50.5), transverse colon (80.6% vs. 68.0%), and left colon (81.5% vs. 67.0%) on the BBPS were significantly higher in the OST group than in the 2 L-PEG/ASC group. However, the rates of successful cleansing according to BBPS (90.7% vs. 91.2%) and HCS (96.3% vs. 94.2%) did not significantly differ between the two groups. The taste, ease, and amount of consumption of the preparation agent; and willingness to repeat colonoscopy with the same agent (89.8% vs. 78.6%, = 0.026) were significantly better in the OST group compared to the 2 L-PEG/ASC group. Adverse events and clinically significant laboratory changes were not significantly different between the two groups. The OST was not inferior to 2 L-PEG/ASC in terms of bowel cleansing efficacy and showed better tolerability when used for bowel preparation for colonoscopy. Clinical Research Information Service Identifier: KCT0005017.